The Students' Perceptions of AI-Generated and Teacher Feedback in English Writing Skills: A Comparative Study - Perdana, Indra; Bungai, Joni; Ilham, Ilham (Jurnal Pendidikan Bahasa Inggris undiksha, 2025)
Both AI and teacher feedback have benefits in improving students' writing skills. However, there are still differences in perception about the effectiveness of each type of feedback in helping students develop their writing abilities. This study aims to compare students' perceptions of the effectiveness of feedback provided by AI and teachers in enhancing writing skills. A descriptive-quantitative research method was used to conduct a survey among 62 eleventh-grade students in Palangka Raya. A Likert scale assessment was used in the questionnaire to evaluate ten indicators, including unity, coherence, content development, grammar, vocabulary, mechanics, personalization ability, response speed, feedback reception, and alignment with learning objectives. The data were analyzed using descriptive statistics and the Wilcoxon signed-rank test, revealing various findings. The results indicate that AI is superior in terms of unity, content development, grammar, mechanics, and response speed, while AI and teachers are considered equally effective in coherence, personalization ability, and alignment with learning objectives. Both sources also show nearly equal effectiveness in vocabulary and feedback reception. In conclusion, AI plays a crucial role in providing fast and structured feedback, yet the teacher's role remains essential in more personal and contextual aspects, highlighting the importance of balancing technology and human interaction in education.